Family-based treatment for young children with OCD : therapist guide - Freeman, Jennifer Beth (Programs that work., 2009)
Obsessive-compulsive disorder (OCD) can develop at a young age and when it does, it can cause significant distress for the child and the family. Parents may be unclear on the nature of OCD symptoms and how to best respond to their child. Family involvement in the child's symptoms may be making the situation worse for the whole family. When treating young children with OCD, it is important to recognize the family component and directly involve parents in treatment. It is also essential to tailor the treatment to a child's age and developmental level. This therapist guide presents a family-based.